(untitled) (Docentes 2.0 Journal, 2025)
The current context, impacted by Information and Communication Technologies, requires professionals with solidly developed digital competencies. Therefore, it is necessary to assess these competencies with relevant instruments. This research aimed to design and validate a test to assess digital security competency in university students in terms of knowledge, ability, and attitude. The research was based on the hypothetico-deductive method, a positivist paradigm, a quantitative approach, and a non-experimental, descriptive, and cross-sectional design. The study involved 269 undergraduate students from the professional programs of hotel and tourism management, business administration, and agroindustrial engineering at a public university in central Peru. While the results indicate that the test items provide adequate discrimination (46%), a lack of balance is observed, as easy-level questions predominate (67%). Regarding reliability, the test is adequate for its intended purpose (0.70, 0.81), and the factor analysis reveals two factors to be evaluated (factor 1: attitudinal domain; factor 2: knowledge and ability domain). In conclusion, the digital security competency test has adequate psychometric properties and can be used with university students.